Exploiting the Potential of Moringa oleifera Oil/Polyvinyl Chloride Polymeric Bionanocomposite Film Enriched with Silver Nanoparticles for Antimicrobial Activity - Musarat Amina; Nawal M. Al Musayeib; Nawal A. Alarfaj; Maha F. El-Tohamy; Hisham E. Orabi; Sarah I. Bukhari; Amany Z. Mahmoud (International Journal of Polymer Science)
The present study focused on the prospect of fabricating a polymeric naturally extracted Moringa oleifera oil bionanocomposite film enriched with silver nanoparticles for antimicrobial activity. In this study, a standard concentration of Moringa oleifera oil (5-10 wt%) was used to fabricate a polymeric bionanocomposite film using polyvinyl chloride (PVC) enriched with silver nanoparticles. The active constituents of the extracted Moringa oleifera oil were verified using gas chromatography-mass spectrometry. Spectroscopic and microscopic techniques, including scanning electron microscopy, X-ray diffraction, and energy-dispersive X-ray analysis, were employed to characterize and study the surface morphology of the fabricated bionanocomposite film. The antimicrobial activity of the fabricated bionanocomposite film was investigated using different strains of bacteria and fungus. The results revealed well-oriented and excellently dispersed silver nanoparticles in the PVC-Moringa oleifera oil matrix. The bionanocomposite was able to inhibit the growth of Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Salmonella typhi, Pseudomonas aeruginosa, Shigella flexneri, and Candida albicans. The combination of nanoparticles with polymers is opening new routes for engineering fixable composites, which showed antimicrobial properties.